Reuse of Brick Waste as a Cheap-Sorbent for the Removal of Nickel Ions from Aqueous Solutions - Mhawesh, Teba Hameed; Abd Ali, Ziad T. (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The potential application of granules of brick waste (GBW) as a low-cost sorbent for removal of Ni+2ions from aqueous solutions has been studied. The properties of GBW were determined through several tests such as X-Ray diffraction (XRD), Energy dispersive X-ray (EDX), Scanning electron microscopy (SEM), and BET surface area. In batch tests, the influence of several operating parameters including contact time, initial concentration, agitation speed, and the dose of GBW was investigated. The best values of these parameters that provided maximum removal efficiency of nickel (39.4%) were 1.5 hr, 50 mg/L, 250 rpm, and 1.8 g/100mL, respectively. The adsorption data obtained by batch experiments subjected to the Three isotherm models called Langmuir, Freundlich and Elovich, The results showed that the Freundlich isotherm model described well the sorption data (R2=0.9176) in comparison with other models. The kinetic data were analyzed using two kinetic models called pseudo-first-order and pseudo-second-order. The pseudo-first-order kinetic model was found to agree well with the experimental data.